FUNGSI KONSTRATIF SAPAAN DI DALAM MASYARAKAT LAMPUNG DAN KOMERING - Rafa Maritza Herga; Marya Utari; Mulyanto Widodo; Rahmat Prayogi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study examines the role of1 greetings in shaping social identity, building a sense of group unity, and creating harmony among 2people in Lampung and Komering communities. In this context, greetings not only serve as conversation starters but also as tools to strengthen cultural rules, social hierarchical structures, and community integration in the Lampung region. This study uses a communication ethnography and discourse analysis approach. Data were collected through direct observation, in-depth interviews with local residents, and text analysis of daily interactions. The results show that in Lampung society, greetings tend to be formal and hierarchical, such as using the words "Pak" or "Bu" to show respect, while in Komering society, greetings are more free and emphasize equality and familiarity to strengthen relationships within the extended family. The constructive function of these greetings is seen in efforts to preserve traditions, reduce conflict, and adapt to changing times. This study helps to better understand Indonesian language culture and suggests steps to preserve traditional greetings so that they are not eroded by the impact of globalization.